2015
DOI: 10.1186/s12889-015-1583-y
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence against female sex workers in The Gambia: a cross-sectional examination of the associations between victimization and reproductive, sexual and mental health

Abstract: BackgroundFemale sex workers (FSW) are a vulnerable population for sexual violence and poor sexual and reproductive health outcomes. Sexual violence against FSW has not been widely studied in The Gambia. This study will report the prevalence of and evaluate the health issues correlated with forced sex perpetrated by clients against FSW in The Gambia, and will secondly aim to inform future research and efforts to improve health outcomes for survivors of violence.MethodsA cross-sectional survey was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 66 publications
1
46
1
1
Order By: Relevance
“…Targets Indicators Related Survey Questions The survey was adapted from studies with FSW across sub-Saharan Africa [16,[33][34][35][36][37] and pre-tested with FSW community members to ensure that questions were understood in English and Sesotho. Topics included socio-demographic characteristics, human rights violations, sexual behaviour, health service access, mental health, social capital, and reproductive health.…”
Section: Goalsmentioning
confidence: 99%
“…Targets Indicators Related Survey Questions The survey was adapted from studies with FSW across sub-Saharan Africa [16,[33][34][35][36][37] and pre-tested with FSW community members to ensure that questions were understood in English and Sesotho. Topics included socio-demographic characteristics, human rights violations, sexual behaviour, health service access, mental health, social capital, and reproductive health.…”
Section: Goalsmentioning
confidence: 99%
“…A study in India showed that fear of violence from both noncommercial partners and clients can deter sex workers from negotiating condom use and accessing STI services for testing and treatment (Deering ). In Gambia, one study found strong linkages between coerced sex/sexual violence and decreased condom use and unintended pregnancy (Sherwood ). Similarly, a study in Uganda revealed that the forced sex, rape, and other forms of physical and sexual violence experienced by FSWs has resulted in an urgent need for safe abortion services in a country where the practice of unsafe abortion is common (Marlow et al.…”
Section: Pregnancy Intentionsmentioning
confidence: 99%
“…Globally, literature has revealed that HIV/STDs risk factors such as work-related violence [11], unwanted pregnancy [12], and condomless sex [13] were associated with mental health problems, and mental health problems in turn may increase the spread of HIV/STDs among FSWs since FSWs with high level of depression symptoms were less likely to use condom consistently or properly [8]. FSWs with mental health problem are more likely to have suicide ideation and attempt [1114].…”
Section: Introductionmentioning
confidence: 99%